Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 5046 species occurrences available in GBIF matching the query: { "and" : [ "Geometry POLYGON((-34.990768 -7.958597,-34.990768 -8.112935,-34.855499 -8.112935,-34.855499 -7.958597,-34.990768 -7.958597))", "HasCoordinate is true", { "or" : [ "BasisOfRecord is Specimen", "BasisOfRecord is Observation", "BasisOfRecord is Literature Occurrence" ] } ] } The dataset includes 5046 records from 69 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0008752-150615163101818/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences